2022
DOI: 10.1155/2022/3997562
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Ferroptosis-Related Prognostic Gene PTGS2 Based on Risk Modeling and Immune Microenvironment of Early-Stage Cervical Cancer

Abstract: Background. Cervical cancer (CC) has long been a concern, as a gynecological cancer type of high-risk. At present, there are few studies on the early detection of CC at the genetic level. The breakthrough is to recognize CC patients tending to have a worse prognosis by checking the expression pattern of ferroptosis-related genes, which enjoy a great potential of being applied to cancer treatment. Methods. Data used in this study was obtained from a series of public online databases, integrated with ferroptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Hypoxia induces resistance to ferroptosis in cervical cancer cells 59 . D‐mannose alleviates osteoarthritis progression via EPAS1 through ferroptosis 60 . EPAS1 promotes ferroptosis via hypoxia‐related genes in clear cell carcinomas 52,53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia induces resistance to ferroptosis in cervical cancer cells 59 . D‐mannose alleviates osteoarthritis progression via EPAS1 through ferroptosis 60 . EPAS1 promotes ferroptosis via hypoxia‐related genes in clear cell carcinomas 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“… 59 D‐mannose alleviates osteoarthritis progression via EPAS1 through ferroptosis. 60 EPAS1 promotes ferroptosis via hypoxia‐related genes in clear cell carcinomas. 52 , 53 Therefore, studying HFRGs is important for clarifying the malignant biological behaviour of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al established a new predictive model that integrated 7 lncRNAs related to ferroptosis through analysis, which improve the predictive value and guided personalized treatment in patients with CC ( Jiang et al, 2022 ). In the study by Zou et al, the ferroptosis-related gene PTGS2 turned out to be a key prognostic gene for an early-stage CC model associated with the immune microenvironment ( Zou et al, 2022 ). Li et al established a ferroptosis score (FerroScore) that was used to predict the sensitivity to chemotherapy and responses to immunotherapy in patients with CC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in head and neck squamous cell carcinoma, ferroptosis and growth inhibition induced by xCT knockdown or the ferroptosis inducer elastin can be reversed by IL-6, thereby promoting tumorigenesis and progression [31]. In cervical cancer, the PTGS2 low expression group has stronger immune activity and higher tumor mutation burden, which is considered to be a risk factor for cervical cancer [32]. Xiao et al demonstrated that NOX4 expression was up-regulated in gastric adenocarcinoma tissue compared with normal gastric mucosal tissue, which can serve as an effective therapeutic target and biomarker for gastric adenocarcinoma [33].…”
Section: Discussionmentioning
confidence: 99%